Finite fuzzy sets, keychains and their applications - Mahlasela, Zuko (Rhodes University, Faculty of Science, Department of Mathematics, 2009)
The idea of keychains, an (n+1)-tuple of non-increasing real numbers in the unit interval always including 1, naturally arises in study of finite fuzzy set theory. They are a useful concept in modeling ideas of uncertainty especially those that arise in Economics, Social Sciences, Statistics and other subjects. In this thesis we define and study some basic properties of keychains with reference to Partially Ordered Sets, Lattices, Chains and Finite Fuzzy Sets. We then examine the role of keychains and their lattice diagrams in representing uncertainties that arise in such problems as in preferential voting patterns, outcomes of competitions and in Economics - Preference Relations.
Keywords: Fuzzy sets; Finite groups; Lattice theory; Economics -- Mathematical models